Diversity Management as a Base of a Business Model - Hernik, Joanna; Bieniecka, Agnieszka (Journal of Corporate Responsibility and Leadership, 2017)
Purpose: A crucial element of any business is seeking competitive advantage by distinguishing itself from other market players. One way to reach this advantage is to choose conception of human resources based on the diversity principle. The purpose of this paper is to establish the characteristics of a business model based on diversity management. Design/methodology/approach: The aim of this article was reached by an analysis of literature on human resources manage-ment, organisational diversity management and business model-ling. The text includes assessments of business models concepts, and conclusions on advantages and disadvantages of a diversity management-based model. The article is theoretical in nature. Findings: In the article it was emphasized that the main rationale for implementing diversity in market activity is to create a support for creativity, innovativeness and, as a result, better efficiency. So, the company generates profits through greater creativity. Apart from the economic results, social outcomes – such as greater job satisfaction and empathy – may be expected. Research and practical limitations/implications: The theoretical framework of this text may be the basis for further practical com-parisons and studies on diversity management. Originality/value: This article summarizes arguments behind the implementation of diversity in business models. Paper type: theoretical study.